2022
DOI: 10.3390/ijerph19148696
|View full text |Cite
|
Sign up to set email alerts
|

Use of Ultrasound-Guided Interfascial Plane Blocks in Anterior and Lateral Thoracic Wall Region as Safe Method for Patient Anesthesia and Analgesia: Review of Techniques and Approaches during COVID-19 Pandemic

Abstract: Ultrasound-guided interfascial plane blocks performed on the anterior and lateral thoracic wall have become an important adjuvant method to general anesthesia and an independent method of local anesthesia and pain management. These procedures diminish the harmful effects of anesthesia on respiratory function and reduce the risk of phrenic nerve paralysis or iatrogenic pneumothorax. In postoperative pain management, interfascial plane blocks decrease the dosage of intravenous drugs, including opioids. They can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…In recent years, S-PIP has been used as an alternative to general anaesthesia in cardiac surgeries with high risk of general anaesthesia [ 20–22 ]. Szamborski et al reported that US-guided S-PIP can be safely preferred in thoracic surgery due to the risks of general anaesthesia procedures during the pandemic period [ 23 ]. Therefore, for the 1st time in our clinic, awake sternal fixation surgery using US-guided S-PIP with titanium plate was performed in a patient with high risk of general anaesthesia due to 2nd cervical vertebral fracture [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, S-PIP has been used as an alternative to general anaesthesia in cardiac surgeries with high risk of general anaesthesia [ 20–22 ]. Szamborski et al reported that US-guided S-PIP can be safely preferred in thoracic surgery due to the risks of general anaesthesia procedures during the pandemic period [ 23 ]. Therefore, for the 1st time in our clinic, awake sternal fixation surgery using US-guided S-PIP with titanium plate was performed in a patient with high risk of general anaesthesia due to 2nd cervical vertebral fracture [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fascial anesthesia was initially developed as a component of multimodal anesthesia serving mainly as a method of intra- and postoperative analgesia [ 33 35 ]. However, some thoracic and abdominal fascial blocks can also be used as the sole method of anesthesia, mainly for less extensive procedures in the thoracic or abdominal region [ 36 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…The transversus thoracic plane block is a problematic block due to the significant vascularization of the site where the block is performed (perforating, intercostal veins, and branches of the internal thoracic artery). In addition, the proximity of the vascular structures of the pleura and pericardium accounts for the difficulty of performing this type of anesthesia, especially when the patient is not under general anesthesia or sedation [ 36 , 57 ]. Although Abdelbaser et al [ 42 ] and Sepolvere et al [ 64 ] described the safety of the transversus thoracis plane block for patients who underwent open cardiac surgery, this applies to the implementation of the blockade in general anesthetized patients, in whom the risk of agitation of anxious patients or severe tachypnea in patients with cardiac failure were eliminated.…”
Section: Discussionmentioning
confidence: 99%
“…Locoregional ultrasound-guided anaesthesia procedures enhanced the reliability of nerve block practice. Such improvements are also extremely useful as an aid or alternative to general anaesthesia in frail patients with reduced cardiorespiratory reserve or those taking chronic therapies with impact on haemostasis [26].…”
Section: Introductionmentioning
confidence: 99%